The Challenges of Learning Loss in English Language Learning at Islamic Higher Education in the Post Pandemic - Susanto Susanto (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Background: The occurrence of the Covid-19 pandemic forced educational institutions to change learning methods and techniques, especially at Islamic universities in Indonesia. Learning loss is a separate obstacle that must be faced after the COVID-19 pandemic. This study aims to describe lecturers' factors, strategies, and roles in dealing with learning loss in learning English at Islamic universities in Indonesia. Methodology: This study examines or interprets written materials based on the context of published records, textbooks, newspapers, periodicals, and articles. This paper's method guided the writing of research-based conclusions. These conclusions defined